ESTIMACIÓN DE KAPLAN MEIER BOOTSTRAP DE LA CURVA DE SUPERVIVENCIA - Tineo Guevara, Freddy (2006)
In this work the function of survival is estimated by means of the non-parametric method known like the Kaplan Meier Bootstrap estimator, under the assumption of asymptotical normality.